Fabrication of 512-Channel Geometrical Passive Breakup Device for High-Throughput Microdroplet Production - Kim, Chul Min (Micromachines (Basel), 2019)
We present a 512-microchannel geometrical passive breakup device for the mass production of microdroplets. The mass production is achieved through the passive breakup of a droplet into two droplets. The microchannel geometry in the microfluidic device was designed and optimized by focusing on stable droplet splitting for microdroplet preparation and minimizing the hydraulic resistance of the microchannel for achieving high throughput; the minimization of hydraulic resistance was achieved by employing analytical approaches. A total of 512 microdroplets could be prepared from a single liquid plug by making the liquid plug pass through nine sequential T-junctions in the microfluidic device, which led to the splitting of droplets. The microfluidic device was fabricated using conventional photolithography and polydimethylsiloxane (PDMS) casting. We estimated the performance of the microfluidic device in terms of the size distribution and production rate of microdroplets. Microdroplets with a diameter of 40.0 ± 2.2 µm were prepared with a narrow size distribution (coefficient of variation (CV) < 5.5%) for flow rates of disperse (Q(d)) and continuous phase (Q(c)) of 2 and 3 mL/h, respectively. Microdroplet production rates were measured using a high-speed camera. Furthermore, monodisperse microdroplets were prepared at 42.7 kHz for Q(d) and Q(c) of 7 and 15 mL/h, respectively. Finally, the feasibility of the fabricated microfluidic device was verified by using it to prepare biodegradable chitosan microspheres.